(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the challenges and opportunities related to enhancing the employment of women graduates from professional educational institutions in Uzbekistan. The study investigates the effectiveness of existing social mechanisms and provides actionable recommendations to improve employment outcomes. It incorporates an analysis of relevant literature, empirical methods, and interviews to propose practical solutions tailored to Uzbekistan’s socio-economic landscape.